ADDITIVE CYTOTOXIC EFFECT OF CISPLATIN AND ANDROGRAPHIS PANICULATA EXTRACT THROUGH THE MODULATION OF APOPTOTIC MARKERS, CYCLIN-D AND VEGF EXPRESSIONS IN SKOV3 OVARIAN CANCER CELL LINE - DIAH, FARA VITANTRI; MAZFUFAH, NUZLI FAHDIA; AROZAL, WAWAIMULI; LOUISA, MELVA; WANANDI, SEPTELIA INAWATI; ARUMUGAM, SOMASUNDARAM; SREEDHAR, REMYA; WUYUNG, PUSPITA EKA (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aims to investigate the possibility of additive cytotoxic effects of cisplatin and Andrographis paniculate (Burm. f.) Nees(AP) via apoptotic, cell cycle and angiogenesis pathways. Methods: CC50 cisplatin, AP and Andrographolide (AG) were determined by the cell viability of SKOV3 after its exposure to these substances. SKOV3 cells were then divided into 6 experimental groups: one negativecontrol group, one with CC50 cisplatin alone, and three where CC50 was combined with CC50 AP, ½CC50 AP, and 1.5CC50 AP, respectively. The additive cytotoxic effect of cisplatin with AP or AG was evaluated through the modulation of several pathways via qRT-PCR of their markers: apoptotic pathways indicated by Bax, BCL2, Caspase 3 and Caspase 9 expression; cell cycle indicated by Cyclin-D expression; angiogenesis pathways by VEGF expression. Results: Cisplatin reduces cell viability to 54%, 37% when combined with AG, and 30%, 23% and 20% with ½CC50 AP, CC50 AP and 1.5CC50 AP, respectively. AG and AP extract decreases SKOV3 cell viability in a dose-dependent manner. Cisplatin combined with AP showed a statistically significant increase in BAX, Caspase 3, Caspase 9 expression and a decrease in BCL2, which indicated synergy in apoptotic pathways. The best result was seen in cisplatin combined with ½CC50 AP. A decrease in Cyclin D and VEGF was seen in all groups, the best seen in ½CC50 AP and CC50 AP, respectively, showing optimal cell cycle arrest and anti-angiogenesis properties when cisplatin is combined with AP extract. Conclusion: Combining cisplatin with AP extract enhanced cell cycle arrest, apoptosis, and anti-angiogenesis properties.